Nitrogen removal characteristics of enhanced in situ indigenous aerobic denitrification bacteria for micro-polluted reservoir source water. (February 2016) - Zhou, Shilei; Huang, Tinglin; Zhang, Haihan; Zeng, Mingzheng; Liu, Fei; Bai, Shiyuan; Shi, Jianchao; Qiu, Xiaopeng; Yang, Xiao
Highlights: The indigenous aerobic denitrifiers were enhanced in situ reservoir system. The enhanced system performed very well in terms of nitrogen and carbon removal. The carbon utilization diversity of the microbial communities varied significantly over the spatial and temporal variation. Abstract: Indigenous oligotrophic aerobic denitrifiers nitrogen removal characteristics, community metabolic activity and functional genes were analyzed in a micro-polluted reservoir. The results showed that the nitrate in the enhanced system decreased from 1.71 ± 0.01 to 0.80 ± 0.06 mg/L, while the control system did little to remove and there was no nitrite accumulation. The total nitrogen (TN) removal rate of the enhanced system reached 38.33 ± 1.50% and the TN removal rate of surface sediment in the enhanced system reached 23.85 ± 2.52%. TN removal in the control system experienced an 85.48 ± 2.37% increase. The densities of aerobic denitrifiers in the enhanced system ranged from 2.24 × 10 5 to 8.13 × 10 7  cfu/mL. The abundance of nir S and nir K genes in the enhanced system were higher than those of in the control system. These results suggest that the enhanced in situ indigenous aerobic denitrifiers have potential applications for the bioremediation of micro-polluted reservoir system.